STEM education resilience in resilient organizations: a systematic review - Dogaru, Mariana; Negreanu, Mirela Cristina; Pisicǎ, Olivia; Pírvu, Alina Florentina (Frontiers in Education, 2026)
The study focuses on the linkages among success in STEM education (Science, Technology, Engineering, and Mathematics), individual student/teacher resilience, and organizational resilience. Based on the present literature, we investigate, above all, risk-preparedness management and adaptability in handling crises to provide threshold considerations of a resilient school. It draws attention to the responsibility of the principal of the school to build a strong environment targeted at both organizational and personal levels. The study reviews 117 papers about STEM education, student resilience, and instructor resilience. These findings imply that legislators should encourage resilience at all levels in the educational system since a strong school system could be necessary for STEM education. From the systematic review, there are direct recommendations for educators and managers on using relationships, resources, and new strategies in their programs that will temporarily promote resilience while making erroneous links between what generates inspirational endurance among STEM academics.